2021
DOI: 10.21037/jtd-20-3159
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and prognostic factors of primary pulmonary lymphoma

Abstract: Background: Primary pulmonary lymphoma (PPL) is a rare extranodal lymphoma originating from the lung, accounting for 0.5-1.0% of primary lung malignant tumors. Previous case reports or cohort studies included a limited sample size; therefore, the understanding of the disease remains inadequate, and clinical data regarding PPL are limited. Methods: Patients with PPL diagnosed histologically and radiologically between January 2000 and December 2019 at our center were retrospectively analyzed. Results: In total, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…33 – 35 Herein, PPL was more frequent in older people, with the age older than 60 years being remarkably linked to dismal prognosis, similar to previous studies. 27 , 36 However, OS was not significantly associated with aggressive lymphomas sex, treatment, stage, histology, and LDH levels, but this did not mean that its OS had no definite effect on prognosis. Due to the relatively small sample size, there is a need for further studies to clarify these findings.…”
Section: Discussionmentioning
confidence: 92%
“…33 – 35 Herein, PPL was more frequent in older people, with the age older than 60 years being remarkably linked to dismal prognosis, similar to previous studies. 27 , 36 However, OS was not significantly associated with aggressive lymphomas sex, treatment, stage, histology, and LDH levels, but this did not mean that its OS had no definite effect on prognosis. Due to the relatively small sample size, there is a need for further studies to clarify these findings.…”
Section: Discussionmentioning
confidence: 92%
“…PPL could be single or multiple, involving one or both lungs, though it can invade the unilateral lobe ( 24 ). Also, the probability of PPL to be affected on the right side is more common compared to the left side (48.9% vs. 43.3%) ( 25 ). The cases reported in this paper were mainly unilateral (n=14/19), with mainly single number of lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a very important feature of 18F-FDG PET/CT is that whole-body imaging is possible with a single scan and comprehensive information can be obtained, which is conducive to the detection of extrapulmonary lesions and plays an important role in the staging of PPL. Moreover, the different stages have different treatment methods, for example, IE˜II1E PPL is mainly treated with surgery ( 25 ). In the current study, one patient was found to have subphrenic lymph nodes with high metabolism, which raised the stage from IE to III ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…[3,4] Nearly half of reported cases of PPL have been asymptomatic at the time of diagnosis, whereas in the others, the presentation has been associated with nonspecific symptoms, including pulmonary findings such as cough, hemoptysis, dyspnea, or chest pain, as well as systemic symptoms like fever, weight loss, and discomfort. [5][6][7] In asymptomatic patients, incidental radiological findings might be the first assessment. Therefore, PPL is usually highly misdiagnosed in clinical practice.…”
Section: Introductionmentioning
confidence: 99%